Perancangan Ui/Ux Untuk Media Tutorial Pembuatan Aset Visual Bagi Orang Tua Penyandang Disabilitas - Nurfarina, Anne; Medyasepti, Frindhinia; Cennywati, Cennywati (Universitas Widyatama, 2022)
Creative Business of Difabel Community or CIDCO is a creative business community parents and children with disabilities, especially mentally and intellectually, in the form of SMEs (Small and Medium Enterprises). These persons with disabilities are managed by their parents, so the management concept of CIDCO is family based. This is in accordance with with the government’s mission as stated in the Law of Disabilities no. 8 of 2016. In practice, parents find it difficult to understand the flow of production management, especially in terms of design concepts, technical manuals or digital visual asset creation. So we need tutorial media with methods that are effective and easy to understand, because the characteristics of parents are still unfamiliar with these three aspects. As the first step, this research aims to design UI/UX as the basic aspect of the tutorial scope includes user compatibility analysis, human computer interaction and UI/UX prototypes. The research method with experimental specifications, where the prototype will be tested on the user so that it can be determined as the basis for the next research, namely the develpoment of tutorial media in the form of an application.